Characters’ politeness strategies in giving command: should translators keep them? - Ardi, Havid; Nababan, M. R.; Djatmika; Santosa, Riyadi (Penerbit Universiti Kebangsaan Malaysia, 2018)
Politeness strategies have been studied from various angles. In literary works, they can be used as a device to frame characterisation. However, in recent times only a few studies have investigated the association of politeness strategies with characterisation as seen from the translation perspective. This article discusses the result of an investigation on how far the translation of politeness markers in giving commands has contributed to the framing of certain characterisation in literary works. A Pragmatic approach is used in this qualitative research to analyse the translation of politeness markers from English to Indonesian. Objective data were collected through purposive sampling from Dan Brown’s novel Deception Point and its two Indonesian versions to obtain information as to which techniques produce better translation quality in both translations. Then, affective data were collected through Focus Group Discussions. The results show that the translation of politeness markers contributed to the characterisation. It was found that established equivalence, variation, and explicitation techniques employed to the translation of politeness markers contributed to the maintenance of characterisation and the translation quality. Meanwhile, addition, reduction, and literal translation techniques altered the characterisations and therefore, decreased the translation quality. This implies that translators should consider politeness and characterisation in translating commands.